A new species of Philodendron (Araceae) in Paraná, Brazil - Buturi, Camila Vanessa; Temponi, Lívia Godinho; Sakuragui, Cassia Mônica (Phytotaxa, 2014)
A new species of Philodendron from the Atlantic Forest in Paraná, Brazil, is described and illustrated. Philodendron meridionale belongs to subgenus Philodendron, section Macrobelium. It is similar to P. loefgrenii, from which it differs by the cordate base and larger number of locules, and is also similar to P. roseopetiolatum, from which it can be distinguished by smaller leaves and obscure primary lateral veins.